2012 IEEE International Conference on Communications (ICC) 2012
DOI: 10.1109/icc.2012.6364846
|View full text |Cite
|
Sign up to set email alerts
|

Fountain code based Adaptive multi-hop Reliable data transfer for underwater acoustic networks

Abstract: In this paper, we investigate multi-hop reliable data transfer for underwater acoustic networks. Due to the unique features of underwater acoustic channels (such as long propagation delays and high channel error rates), conventional reliable data transfer approaches (such as simple transmission-upon-failure and coding) cannot be directly applied underwater. In addition, the strong property of half-duplex transmission of current acoustic modems requires joint optimization for a multi-hop network scenario in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The distance of each hop is uniformly distributed between 2 and 5 km. The transition delay between the sending and receiving status of the acoustic modem is selected to be 1.5 s, modem synchronization delay is 0.5 s and forwarding delay is 1 s [22,23]. The initial energy of each node is assumed to be 70 J [56].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The distance of each hop is uniformly distributed between 2 and 5 km. The transition delay between the sending and receiving status of the acoustic modem is selected to be 1.5 s, modem synchronization delay is 0.5 s and forwarding delay is 1 s [22,23]. The initial energy of each node is assumed to be 70 J [56].…”
Section: Resultsmentioning
confidence: 99%
“…In [20], the authors employ fountain code to enhance the reliability and efficiency of broadcasting in UASNs, while in [21], the authors use fountain codes for reliable data transport and storage. In [22], the authors propose fountain code-based adaptive multi-hop reliable data transfer (FOCAR), a hybrid ARQ scheme which integrates Fountain codes with hop-by-hop retransmission upon failure, for reliable data transfer in UASN. In [23], the authors propose a practical coding multi-hop reliable data transfer (PCMRDT) protocol for UASN that combines random linear coding and hop by hop selective repeat retransmission scheme to achieve high reliability.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…CFP [31] integrated optimal probabilistic forwarding scheme with fountain codes to reach better delivery ratio, avoiding the waste of the resources. FOCAR was proposed to obtain high reliability and low end-to-end delay [32]. In addition, it was shown that fountain coding could improve the data delivery in VANETs compared to other traditional protocols [4].…”
Section: Fountain Codesmentioning
confidence: 99%
“…In [13], the authors addressed the energy issues in UWSN and proposed methods to estimate the battery lifetime and power cost of shallow water networks. Reliable data transfer which is aimed to provide reliable service to the upper-layer applications has also been investigated in [14][15][16].…”
Section: Introductionmentioning
confidence: 99%